The Political Economy of Arms Export Restrictions: The Case of Japan - TAGO, ATSUSHI; SCHNEIDER, GERALD (Japanese Journal of Political Science, 2012)
The export of arms belongs to the most contested issues in democracies. In this article, we examine the economic repercussions of the recent easing of the Japanese arms exports restrictions. We develop a rational expectations argument to understand why some political events increase the income of the arms manufacturers, while other ones reduce it or have no effect at all. Event studies suggest that investors closely observe relevant political developments since stock prices of the six arms manufacturers companies reacted consistently to the announcements and leaks as to whether the arms export restrictions would be lifted or not.